Comparative Study of P&O and Modified Incremental Conductance Algorithm In Solar Maximum Power Point Tracking - Tiong, Meng Chung; Hamdan, Daniyal; M. H., Sulaiman; Mohd. Shafie, Bakar (2016)
Photovoltaic (PV) system has been widely used as one of the renewable energy resources. Due to the non-linear I-V characteristic and changes of the external environment and load, the output power of the PV array varies according to different situation. Hence, the maximum power point (MPP) tracking technology is necessary to be implemented in order to track for the only MPP on the P-V curve to increase the energy harness from the PV array. In this study, two commonly used MPPT algorithm, perturb and observe and incremental conductance were developed in Matlab Simulink with a boost DC-DC converter to study the accuracy, speed and tracking efficiency under STC, slow changing irradiance condition and step changing irradiance condition. Comparative studies shows that modified incremental conductance is able to track MPP faster and more efficiently under fast changing of irradiance.